Strategi Pengembangan Program Baca Kitab Kuning di Madrasah Diniyah Kota Tegal - Ikfina ‘Aisyatus Shidqy; Nada Maulida; Nailis Silmi; Siti Nurasiah; Ummu Salmaa’ (La-Tahzan: Jurnal Pendidikan Islam, 2023)
Diniyah Madrasah is one of the Islamic educational institutions that has its own characteristics, including the yellow book reading program in the teaching and learning process. There must be a strategy in developing the reading program.  This research aims to find out how the strategy of the Tegal City Diniyah Madrasah in developing the yellow book reading program as well as the supporting and inhibiting factors. The approach and type of this research is descriptive qualitative. The result of this research is the strategy in Madrasah Diniyah Istiqomah Tegal City, implementing strategies in the form of Sorogan system, memorization, data collection, permanent teachers. The inhibiting factor is the difficulty of recruiting students so that the assatidz need to adjust. The conclusion that can be drawn is that the Istiqomah Madrasah has a goal of making yellow book learning as one of the compulsory lessons that must be followed by every santri and by reading Javanese religious books and Arabic scriptures, it is hoped that students will gain an understanding of the contents of the book, and deepen religious knowledge.